UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MELALUI METODE PEMBELAJARAN TANYA JAWAB PADA PESERTA DIDIK KELAS IV SDN 35 SUNGAI LIMAU - Ernita, Ernita (Jurnal Manajemen Pendidikan, 2017)
The success of the learning objectives is determined by many factors including the teacher factor in implementing the teaching and learning process, because teachers can directly influence, foster and improve the intelligence and skills of learners. To overcome the above problems and to achieve the goal of education maximally, the role of teachers is very important and it is expected that teachers have a good method of teaching and able to choose the right method of learning and One of the appropriate learning model on learning Indonesian is the method of pembelajaran tanya jawab.Permasalahan which wanted to be studied in this research is: Whether through the use of question and answer learning method can improve learning outcomes Indonesian learner Class IV SDN 35 Sungai Limau The purpose of this action research is to improve the learning outcomes of Indonesia through the use of question and answer learning methods in participants educated SDN 35 Sungai Limau. This study used a classroom action research of two rounds. Each round consists of four stages: planning, execution, observation, reflection. The target of this research is students of Class IV SDN 35 Sungai Limau. The data obtained are quantitative and qualitative data. From the analysis of question and answer learning method has positive impact in improving learners 'learning result which is marked by the improvement of students' learning mastery in every cycle, that is Pre cycle (58.14%), cycle I (72.09% ), cycle II (97.67%). The conclusion of this research is the method of question and answer learning has a positive influence, that is can improve learners' learning outcomes that are indicated by the average answers of learners that states that learners are interested and interested in the method of question and answer learning so that they become motivated to learn.